Designing Asset-Based Community Participatory Planning through an Appreciative Inquiry Approach in a Stunting Prevention Project at the Usaha Mulia Cipanas Foundation - Nau, Patrick Alexander; Aribowo, Aribowo; Kuswanda, Dede (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
Yayasan Usaha Mulia (YUM) in Cipanas, Cianjur Regency, implemented a stunting prevention project in its working area which was carried out in a one-year program period from the initial stage to the final stage. The stunting prevention project was carried out through assistance to integrated health posts by providing training for cadres, providing nutritional aid to pregnant and breastfeeding mothers, providing complementary food assistance for breast milk for babies, providing health education and counseling for pregnant and breastfeeding mothers, providing free ultrasound examination assistance, providing cooking class training for breastfeeding mothers and providing additional incentives for integrated health post cadres. The purpose of this study was to determine and improve the development of participatory planning design based on community assets through an appreciative inquiry approach in the stunting prevention project implemented at YUM. This study uses a qualitative approach with the Participatory Action Research (PAR) method through Focus Group Discussion (FGD) techniques, in-depth interviews, observations, documentation studies, and literature review. The primary data sources in this study were participants consisting of YUM project managers, YUM project officers, integrated health post cadres, community leaders, and village government officials. The study began with a reflection on the initial design, then identified and formulated design improvement needs and prepared a design development plan based on needs. After the design was formed, the design draft was implemented at the research locus and ended with an evaluation to obtain recommendations for design improvements. The results of the implementation of the technology engineering design showed that the participatory planning design based on community assets through an appreciative inquiry approach in the stunting prevention project could support the sustainability of the program after the termination of services from YUM.